2012
DOI: 10.5543/tkda.2012.01679
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow-up of 799 children with isolated ventricular septal defects

Abstract: Our data on the natural course and prognosis of VSDs may be of relevance with respect to patients' age, defect type, and complications encountered in the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
3
7
0
2
Order By: Relevance
“…From a clinical point of view, interpretation of data may be challenging. It is known that in case of large to moderate perimembranous and subarterial VSDs follow‐up is warranted for possible complications such as aortic valve prolapse, aortic regurgitation left ventricle‐to‐right atrium shunt, subaortic ridge, and infundibular stenosis . We did not experience similar complications but our series involved mainly small VSDs, with the follow‐up of only two large and 19 moderate sized VSDs.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…From a clinical point of view, interpretation of data may be challenging. It is known that in case of large to moderate perimembranous and subarterial VSDs follow‐up is warranted for possible complications such as aortic valve prolapse, aortic regurgitation left ventricle‐to‐right atrium shunt, subaortic ridge, and infundibular stenosis . We did not experience similar complications but our series involved mainly small VSDs, with the follow‐up of only two large and 19 moderate sized VSDs.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies, instead, have a limited follow‐up period . There are only few studies evaluating the natural history of all types of neonatal VSDs and with a long follow‐up period (ie, >2 years) …”
Section: Discussionmentioning
confidence: 99%
“…The results from the data confirmed that the ratio of the diameter of the aorta to that of the pulmonary artery in TOF is disproportional due to the uneven separation of the circular trunk. Growth of the pulmonary artery is limited, while that of the aorta is fast 7 . Therefore, the ratio of the aortic diameter to the pulmonary artery diameter is increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Closure occurred most frequently at the midmuscular location, while apical defects persisted more often (7,8). Age at first echocardiographic examination and the length of the follow-up period may influence the spontaneous closure rate (9,10). It has been demonstrated that 12.5-31% of m-VSDs can undergo spontaneous closure during fetal life (11,12).…”
Section: Discussionmentioning
confidence: 99%